Quantitative considerations on the recent evolution of the conflict (2009)
The present article starts with a quantitative remark of the elevated Colombian expense in defense, one of the highest worldwide in percentage of the GNP. What greatly worries is that most of such expenditure is addressed to the payment of retirement wages in the armed forces, becoming the number one budgeted institution in the country given the excessive increase in troops, a fact that ranks Colombia as the Latin-American country with the second largest army after Brazil. There would be, then, a difference between military success (effectiveness) and increase in troops, since according to government’s numbers, the guerillas should be practically terminated, not being the real fact. Two possible explanations for this difference exist: first, demobilization of the paramilitary groups, whose action and combatants reinforced the duty of the military forces; and second, the evidence of extra judiciary executions and the making of false positive hits, all of which would be inflating the figures that intend to show the effectiveness of military actions.